55.2k views
2 votes
For g(x) = 4x-9 Find g(x) When X=3 And When X=5 I Need Help Again I Don't Get This One Either!

User TDrabas
by
5.5k points

1 Answer

7 votes

Hey there!


Let's first solve g(x) when x = 3.

The first step is to change wherever it says x in the equation to 3, because that is the value we are solving for.

g(3) = 4(3) - 9

Next, we can multiply 4 by 3, because multiplication comes before subtraction in PEMDAS.

g(3) = 12 - 9

Lastly, we can subtract 9 from 12 to get the final value.

g(3) = 3 So, the value for g(x) when x = 3 is 3.


Now, we'll solve for g(x) when x = 5.

The first step is to change wherever it says x in the equation to 5, because that is the value we are solving for.

g(5) = 4(5) - 9

Next, we can multiply 4 by 5, because multiplication comes before subtraction in PEMDAS.

g(5) = 20 - 9

Lastly, we can subtract 9 from 20 to get the final value.

g(5) = 11 So, the value for g(x) when x = 5 is 11.


Hope this helps!

User Cfnerd
by
6.0k points